Human papillomavirus and p53 expression in cancer of unknown primary in the head and neck region in relation to clinical outcome. (10th February 2014) - Sivars, Lars; Näsman, Anders; Tertipis, Nikolaos; Vlastos, Andrea; Ramqvist, Torbjörn; Dalianis, Tina; Munck‐Wikland, Eva; Nordemar, Sushma
Abstract Patients with cancer of unknown primary (CUP) in the head neck region are generally treated with neck dissection followed by radiotherapy at times combined with chemotherapy, a treatment associated with considerable side effects. Some of these tumors may originate as human papillomavirus (HPV)‐positive oropharyngeal squamous cell carcinoma (OSCC), with better clinical outcome than head neck squamous cell cancer (HNSCC) in general, and could potentially do well with less treatment. Here, we therefore investigated whether HPV status and p53‐expression correlated to clinical outcome in patients with CUP in the head neck region. Fifty metastases were analyzed for presence of HPV DNA, and expression of p16INK4A and p53 and the data were correlated to clinical outcome. Patients with HPV DNA‐positive (HPVDNA+) metastases had significantly better 5‐year overall survival (OS) compared to those with HPVDNA− metastases (80.0% vs. 36.7%, respectively; P = 0.004), with a similar tendency for disease‐free survival (DFS). These survival rates showed excellent concordance with those of HPVDNA+ and HPVDNA− OSCC in Sweden during the same time period, strengthening the hypothesis that HPVDNA+ head and neck CUP may originate from HPVDNA+ OSCC. In addition, having absent/intermediary‐low as compared to high expression of p53 correlated to a better prognosis with a 69% as compared to 14% 5‐year OS, respectively (P < 0.001), and for DFS the tendency was analogous. In conclusion, both HPV status and p53 expression are valuable prognostic factors in patients with CUP in the head and neck region and should be further explored for clinical use.